EFEKTIVITAS PELATIHAN GURU TERHADAP PENINGKATAN KOMPETENSI LITERASI NUMERASI DI SEKOLAH DASAR - Adinda Ratu Puri; Cut Rafa Auliya Qolby; Elisabeth Helsa Kurnia; Nurul Pitriyani; Tia Citra Bayuni (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to analyze the effectiveness of teacher training in improving numeracy literacy competence in elementary schools. Numeracy literacy is a fundamental skill that enables students to understand, interpret, and apply numerical concepts in everyday life. The low achievement of numeracy literacy at the elementary level indicates the need to strengthen teachers’ capacity as learning facilitators. This research employed a quantitative method using a pretest-posttest design on a group of elementary school teachers who participated in a training program. Data were collected through competency tests, classroom observations, and participant questionnaires. The results showed a significant improvement in teachers’ competencies after attending the training, as indicated by the increase in posttest scores compared to pretest scores. In addition, teachers demonstrated better skills in designing context-based numeracy learning and implementing numeracy literacy strategies in the classroom. Therefore, teacher training was proven effective in enhancing numeracy literacy competence in elementary schools and had a positive impact on improving the quality of teaching and student learning outcomes.